A presença dos adolescentes no Centro Integrado de Educação de Jovens e Adultos (CIEJA): a perspectiva dos docentes - Ferreira, Alexandre Fausto (2018)
The present investigation discussed about a demand brought by the partner institution for this study, the Integrated Center of Education for Young and Adults (Centro Integrado de Educação de Jovens e Adultos – CIEJA), located in the north zone of São Paulo, which demanded the need of understanding the participation of teenagers and their massive arrival in the institution. This problem is interconnected to structural issues that go through the Young and Adults Education (Educação de Jovens e Adultos – EJA) and, in this way, influenced manly for the teenagers early leaving from regular primary and high school. This is an qualitative interventionist research based on a phenomenological-existential perspective, illuminated by the philosopher Martin Heidegger’s (1889-1976) thoughts and support of Merleau-Ponty’s (1908-1961) ideas. The main goal is to comprehend, in an interventive process, the participation of teenagers at CIEJA from the teacher’s point of view. As specifics: [a] Create psychoeducational and dialogic areas for listening and reflection co-built with the scholar staff; [b] promote specific discussion opportunities about teenagers in the Institution. From the interventionist perspective of this investigation, two reflexive meetings were organized with the school staff (SZYMANSKI and SZYMANSKI, 2014). These meetings were recorded and transcripted and its content made possible to organize three topics: (a) Youth and Vulnerability: school staff perspective; (b) CIEJA as the care and dialogue’s place; (c) Talking about daily teacher’s dilemmas with the teenagers. In general, it was observed that investments in reflection dialogue spaces about teenagers’ participation in the institution could be a vector of collective constructions to support these people. Although teachers suffer the daily wearing out caused by several structural issues which deteriorate their work conditions, there is a tendency of the teacher about the teenagers’ permanent demands. The results show that there is a teacher’s understanding of the vulnerable condition of these teenagers caused by a violent process of exclusion from the regular education